Relapse of acute malnutrition and associated factors after discharge from nutrition stabilization centers among children in Eastern Ethiopia - Alyi, Mohammedjemal; Roba, Kedir Teji; Ketema, Indeshaw; Habte, Sisay; Goshu, Abel Tibebu; Mehadi, Ame; Baye, Yohannes; Ayele, Behailu Hawulte (Frontiers in Nutrition, 2023)
Background Acute malnutrition is a major global health problem primarily affecting under-five children. In sub-Saharan Africa, children treated for severe acute malnutrition (SAM) at an inpatient have high case fatality rate and is associated with relapse of acute malnutrition after discharge from inpatient treatment programs. However, there is limited data on the rate of relapse of acute malnutrition in children after discharge from stabilization centers in Ethiopia. Hence, this study aimed to assess the magnitude and predictors of relapse of acute malnutrition among children aged 6–59 months discharged from stabilization centers in Habro Woreda, Eastern Ethiopia. Methods A cross-sectional study was conducted among under-five children to determine the rate and predictors of relapse of acute malnutrition. A simple random sampling method was used to select participants. All randomly selected children aged 6–59 months discharged from stabilization centers between June 2019 and May 2020 were included. Data were collected using pretested semi-structured questionnaires and standard anthropometric measurements. The anthropometric measurements were used to determine relapse of acute malnutrition. Binary logistic regression analysis was used to identify factors associated with relapse of acute malnutrition. An odds ratio with 95% CI was used to estimate the strength of the association and a p-value less than 0.05 was considered statistically significant. Results A total of 213 children with mothers/caregivers were included in the study. The mean age in months of children was 33.9 ± 11.4. More than half (50.7%) of the children were male. The mean duration of children after discharge was 10.9 (± 3.0 SD) months. The magnitude of relapse of acute malnutrition after discharge from stabilization centers was 36.2% (95% CI: 29.6,42.6). Several determinant factors were identified for relapse of acute malnutrition. Mid-upper arm circumference less than 110 mm at admission (AOR = 2.80; 95% CI: 1.05,7.92), absence of latrine (AOR = 2.50, 95% CI: 1.09,5.65), absence of follow-up visits after discharge (AOR = 2.81, 95% CI: 1.15,7.22), not received vitamin A supplementation in the past 6 months (AOR = 3.40, 95% CI: 1.40,8.09), household food insecurity (AOR = 4.51, 95% CI: 1.40,15.06), poor dietary diversity (AOR = 3.10, 95% CI: 1.31,7.33), and poor wealth index (AOR = 3.90, 95% CI: 1.23,12.43) were significant predictors of relapse of acute malnutrition. Conclusion The study revealed very high magnitude of relapse of acute malnutrition after discharge from nutrition stabilization centers. One in three children developed relapse after discharge in Habro Woreda. Programmers working on nutrition should design interventions that focus on improving household food insecurity through strengthened public Safety Net programs and emphasis should be given to nutrition counseling and education, as well as to continuous follow-up and periodic monitoring, especially during the first 6 months of discharge, to reduce relapse of acute malnutrition.